2013
DOI: 10.4018/jec.2013040102
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Constraints

Abstract: This research focused on the question: What leadership constraints contribute to the complexity of the working environment faced by global virtual team leaders and how do those leadership constraints impact the behavior of leaders when they are trying to meet team member expectations? This qualitative study of a high performing team within a multinational corporation (MNC) identified four constraints facing leaders: virtuality, globalization, the domestic workplace, and the matrix organizational structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…Moreover, flexible work arrangements give a more general perspective of telecommuting, as they not only include telecommuting but also diverse flexible work programs such as flextime and compressed work weeks. At last, virtual work is referred to the work activities performed by individuals, or teams, who work together in a virtual environment using information and communication technologies, due to the geographic distance (Tworoger et al. , 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, flexible work arrangements give a more general perspective of telecommuting, as they not only include telecommuting but also diverse flexible work programs such as flextime and compressed work weeks. At last, virtual work is referred to the work activities performed by individuals, or teams, who work together in a virtual environment using information and communication technologies, due to the geographic distance (Tworoger et al. , 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The Mann–Whitney is a nonparametric test to discover differences between two independent samples and is a nonparametric equivalent of the independent t –test (Field). In an online questionnaire on bullying conducted with graduate students, Yamada et al (2014) conducted data analyses with Mann–Whitney and Kruskal–Wallis tests to accommodate the nonnormal distribution of their research data. Our study has a similar issue with data; hence the decision to use Kruskal–Wallis and Mann–Whitney tests.…”
Section: Rationale For Statistical Testsmentioning
confidence: 99%
“…Yet, along with the growing prevalence of GVTs and their potential benefits to organizations, research indicated that virtual teams were more difficult to manage than colocated teams (Dulebohn & Hoch, 2017;Hoch & Koslowski, 2014;Krumm et al, 2013). A number of factors were found to negatively affect the performance of GVTs, including language and cultural differences, technological limitations, lack of role clarity, lack of trust, difficulties working across time zones, (Hoch & Koslowski;Krumm et al, 2013;Maynard, Mathieu, Rapp & Gilson, 2012), stress due to lack of boundaries between personal and professional identities in the 24/7 virtual environment (Shaik et al, 2021) and unforeseen implications of the power dynamics that shape the contexts in which the teams must work (Lockwood, 2015;Tworoger, Ruppel, Gong & Pohlman, 2013;Zakaria & Ab Rahman Muton, 2022). Cross-cultural factors may be particularly important on GVTs, not only because cultural differences may be more salient on virtual teams than on co-located teams (Krumm et al, 2013), but also because members are frequently unprepared for cross-cultural interactions (RW 3 CultureWizard, 2022).…”
Section: Significance Of the Researchmentioning
confidence: 99%
“…However, there was little in the literature that illuminates how such superordinate identities might be established. Some studies recommended up front, face to face team-building events to establish a strong team identity and clarify roles (Duranti & Almeida, 2012;Henderson et al, 2016;Tworoger et al, 2013). Others suggested emphasizing professional identities and expertise by creating channels of communication, particularly through the use of rich media, to allow individuals to naturally follow their professional curiosity and ambitions (Materelli et al, 2017) and build competence-based trust through frequent interaction with professional peers (Olaisen & Revang).…”
Section: Preventing Subgroup Formationmentioning
confidence: 99%
See 1 more Smart Citation